From Islamism to Neo-Islamism: Political Exegesis in Sayyid Quṭb and Majd Makkī - Abu Sufyan; Mohammad Yunus; Ibnu Burdah (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2025)
This article examines the political and ideological dimensions of contemporary Sunni Qur’anic exegesis through a comparative analysis of Sayyid Quṭb and Majd Makki. It focuses on Fī Ẓilāl al-Qur’ān and al-Mu‘īn ‘alā Tadabbur al-Kitāb al-Mubīn to explore how each scholar articulates the relationship between scripture and political order. The study employs a qualitative library-based approach, using comparative content analysis to examine key themes, interpretive strategies, and socio-political contexts shaping both works. The findings show that Quṭb advances a movement-oriented hermeneutics (manhaj ḥarakī) that frames the Qur’an as a basis for systemic resistance against secular authority through the concept of ḥākimīyah. In contrast, Makki develops a contemplative (tadabbur-based) approach that increasingly incorporates themes of democracy, pluralism, and anti-authoritarianism, particularly in response to the Syrian revolution and its digital discourses. This study argues that the contrast between the two reflects a broader shift in Sunni political exegesis from ideological, system-driven Islamism toward a more pragmatic and context-responsive neo-Islamism. It contributes to the study of religion and politics by demonstrating how Qur’anic interpretation functions as a dynamic site of ideological negotiation and political praxis in the modern Muslim world.